Physicochemical, fatty acid and antioxidant properties of passion fruit (Passiflora species) seed oil - Ramaiya, Shiamala Devi; Bujang, Japar Sidik; Zakaria @ Ya, Muta Harah (ANSI Network, 2019)
Background and objective: the passion fruit industry uses half of the fruit mass for juice extraction, while the rest represents an agricultural by-product that consists of rinds and seeds. Generally, the seeds are disposed of after being crushed, causing a substantial burden on the environment. Thus, efforts have been made to utilize the seeds for useful resources. This study focused on the physicochemical characteristics, fatty acid and antioxidant properties of seed oil extracted from three Passiflora species [P. edulis Sims (Purple), P. quadrangularis and P. maliformis]. Materials and methods: Passiflora seed oil was extracted using petroleum ether as a solvent and analysed for its physicochemical properties: refractive index, specific gravity, iodine value, saponification value, non-saponification matter, acid value, peroxide value and free fatty acid content. The fatty acid composition and antioxidant properties were also analysed. Results: Passiflora seeds were rich in oil content, yielding 24 30%. The Passiflora seed oil also possessed high values of iodine (124.67±0.67-131.00±0.58 g I2 100 gG1 ) and peroxide (1.43±0.12-3.23±0.12 meq kgG1 ) similar to other edible seed oils, e.g., sunflower. The seed oil contained essential fatty acids with a higher proportion of unsaturated fatty acids (>80%), mostly comprising linoleic and oleic acid. Passiflora edulis (Purple) seed oil had a comparatively higher total phenolic content (570.74±0.78 mg kgG1 ) and stronger antioxidant activity (33.63±1.46 mg mLG1 ). Based on principle component analysis (PCA), the biplot generated showed that Passiflora seed oils possessed characteristics similar to those of sunflower and soybean oils. Conclusion: the present findings revealed that the oil of Passiflora seeds, an agro by-product, is valuable and can be extracted for nutraceutical and pharmaceutical uses.